Rola miast w polityce spójności Unii Europejskiej w latach 2007-2013 - Ryszawska-Grzeszczak, Bożena (The Role Cities in the European Union Cohesion Policy 2007-2013, 2008)
The Commission accepted in 2006 the new program "Cities and cohesion Policy 2007-2013". Cities play a key role in shaping the European economy. Cities are home to most jobs, businesses and higher education institutions which is important to stimulate the knowledge-based economy. They have been and they will be the engines for regional, national, and European economic growth. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 207-216